Molecular cloning and long terminal repeat sequences of human endogenous retrovirus genes related to types A and B retrovirus genes. - Ono, M (1986)
By using a DNA fragment primarily encoding the reverse transcriptase (pol) region of the Syrian hamster intracisternal A particle (IAP; type A retrovirus) gene as a probe, human endogenous retrovirus genes, tentatively termed HERV-K genes, were cloned from a fetal human liver gene library. Typical HERV-K genes were 9.1 or 9.4 kilobases in length, having long terminal repeats (LTRs) of ca. 970 base pairs. Many structural features commonly observed on the retrovirus LTRs, such as the TATAA box, polyadenylation signal, and terminal inverted repeats, were present on each LTR, and a lysine (K) tRNA having a CUU anticodon was identified as a presumed primer tRNA. The HERV-K LTR, however, had little sequence homology to either the IAP LTR or other typical oncovirus LTRs. By filter hybridization, the number of HERV-K genes was estimated to be ca. 50 copies per haploid human genome. The cloned mouse mammary tumor virus (type B) gene was found to hybridize with both the HERV-K and IAP genes to essentially the same extent.